Social capital in rural southwest Kansas. - Bolton, Debra J. (Kansas State University, 2011)
This study addresses a social capital literature that has mostly targeted a White majority population in the United States. Hispanic audiences, especially new immigrant populations, have not been primary survey respondents in most studies. Information about the social connectedness of minorities has come from secondary sources. The goal of this study was to understand to what extent Hispanic, compared to Anglo, families in rural Kansas experienced different levels of social capital in terms of social connectedness and community involvement. This study was done in English and Spanish in order to reach the under-represented population. According to political scientist, Robert Putnam (2000), it is through experiences of face-to-face interaction with those from different backgrounds that people learn to trust each other. Connections create networks that allow social trust to spread throughout society. At the individual level, there has been strong, consistent evidence that social connectedness has positive consequences. Individuals have the capacity and the choice to build their social connectedness and community engagement. Then those assets can be shared with the collective; be it family, organization, community, state, or country. When individuals have access to networks of supportive and accepting associates, it can generate an array of personal and societal benefits that include preventing or overcoming illness, preventing crime, mitigating poverty, addressing racial inequalities, supporting child development, improving health, and addressing other social ills. When one builds a stock of personal relationships and other social connections from which he or she can call upon in times of need, it is called social capital. This study, in part, assessed social connectedness and community engagement of people in Southwest County, a rural location in Southwest Kansas which has a 30% Hispanic population. Surveys were sent to selected households in English and Spanish, and two small focus groups were conducted in the two languages. Statistical analyses indicated support for the hypotheses when the independent variables gender, age, race/ethnicity, education, income, and community longevity were analyzed with dependent variables made up of scaled items to measure social connectedness and community engagement. Race/ethnicity, education, and income appeared to be the strongest predictors of social connectedness and community engagement. Implications of the results are discussed.
Keywords: Social capital; Hispanic/immigrant populations; Community involvement; Rural communities; Social interaction; Social Research (0344)